Evaluating the impact of HIV pre-exposure prophylaxis on pregnancy, infant, and maternal health outcomes in Malawi: PrIMO study protocol - Friday Saidi; Sanya Shah; Madeleine Squibb; Lameck Chinula; Charity Nakanga; Tisungane Mvalo; Mitch Matoga; Agatha K. Bula; Maganizo B. Chagomerana; Funny Kamanga; Wiza Kumwenda; Tawonga Mkochi; et al. (BMC, 2024)
Abstract Background Incident HIV during the perinatal period significantly impedes elimination of Mother-to-Child HIV Transmission (eMTCT) efforts. Pre-Exposure Prophylaxis (PrEP) effectively reduces HIV acquisition, and new agents like injectable Cabotegravir (CAB-LA) offer potential advantages for pregnant and breastfeeding women. The Pregnancy, Infant, and Maternal health Outcomes (PrIMO) study will compare rates of composite adverse pregnancy outcomes, and infant adverse events, growth and neurodevelopment between mother-infant dyads receiving CAB-LA and those receiving oral PrEP in Malawi. Methods PrIMO is an observational cohort study involving: (1) the development of a PrEP Pregnancy Registry for longitudinal surveillance of pregnant women on PrEP in Malawi; and (2) the enrolment of a prospective safety cohort of 621 pregnant women initiating oral PrEP or CAB-LA and their subsequent infants. The registry will include all women continuing or initiating PrEP during pregnancy across targeted sites in Lilongwe and Blantyre districts. The safety cohort will enrol a subset of those women and their infants from Bwaila District Hospital in Lilongwe, Malawi. We hypothesize that CAB-LA's safety will be comparable to daily oral PrEP regarding adverse pregnancy outcomes, maternal/infant adverse events, and infant development. Participants in the cohort will choose either oral PrEP or CAB-LA and will be followed until 52 weeks post-delivery. Safety data will be collected from all mother-infant pairs and qualitative interviews will be conducted with a subset of purposively selected women (n = 50) to assess the acceptability of each PrEP modality. Discussion The PrIMO study will provide critical data on the safety of CAB-LA in pregnant and breastfeeding women and their infants. Results will guide clinical recommendations as the Malawi Ministry of Health prepares for the rollout of CAB-LA to this population. Evaluation of Registry implementation will inform its expansion to a nationwide safety monitoring system for PrEP use during pregnancy, with implications for similar systems in the region. Trial Registration number NCT06158126. The study was prospectively registered (5 December 2023) in ClinicalTrials.gov.